THE WINEMAKING INDUSTRY IN THE SOCIETY OF JESUS’ PROPERTIES IN SANTIAGO OF CHILE. A BIBLIOGRAPHICAL REVISION. - Sottorf Neculhueque, Carlos (Revista de Historia Social y de las Mentalidades, 2024)
This article seeks to approximate way how the Society of Jesus started to develop an important economic power in Chile since the late XVI century, based especially on farming properties and production, with especial emphasis on wine production. The Society of Jesus acquired properties, and some of them reached important levels in terms of production and administration, being wine production one of the many branches in their enormous trading web. It is important to highlight the importance wine had for the Society of Jesus, since it was used as a payment mean in agricultural activities, such as the rodeo and harvests. In this manner, the winemaking activity it is portrayed as part of the diversification of the productive units of the company, which improved their harvest techniques and, therefore, increased their productive rates outstandingly.